Gastrointestinal haemorrhage from a jejunal gangliocytic paraganglioma. Issue 1 (January 1995) - Aung, W; Gallagher, H J; Joyce, W P; Hayes, D B; Leader, M
Abstract : A case of jejunal gangliocytic paraganglioma is reported in a 54 year old woman who presented with brisk melaena. The tumour was not encapsulated, involved the mucosa and submucosa, and was composed of epithelial nests, spindle cells, and ganglion cells. These cells were mixed, giving carcinoid-like, paraganglioma-like, and ganglioneuroma-like patterns in different areas of the tumour. The lesion was excised locally and recovery was uneventful. Only four previous cases have been reported at this site.